A cooperative assessment and evaluation scheme of ABET student outcomes in ECE program at Sultan Qaboos University: a case study. (2016) - Mnif, FaÁ¯Á§al; Hosseinzadeh, Nasser
The development and implementation of a systematic process for the assessment and evaluation of student outcomes (SOs) in the electrical and computer engineering (ECE) program at Sultan Qaboos University (SQU) in Oman is described in this case study. Unlike in other programs aiming for ABET accreditation, the process is based on a cooperative and acquiescent approach that involves most of the faculty members, while a majority of faculty members take part in the evaluation process. To achieve this, SO focus groups of faculty members have been formed. Each focus group is chaired by a faculty member who coordinated a SO focus group. An SO focus group is composed of three to four members who carry out the evaluation of the SO. Moreover, for each course, course focus groups were formed to take the responsibility of implementing the recommendations on the respective courses. The proposed strategy led to a systematic continuous improvement process of the ECE program at SQU.